Bi-directional associations between overweight and health-related quality of life from 4-11 years: Longitudinal Study of Australian Children - Jansen, P; Wake, M; Nicholson, J; Mensah, F; Clifford, S (My University, 2013)
BACKGROUND: Temporal pathways of known associations between overweight and poor health-related quality of life (HRQoL) in adolescents remain poorly documented. This study aims to (1) examine timing and strength of the association between HRQoL and body mass index (BMI) in childhood, and (2) investigate directionality and impact of cumulative burden in any observed HRQoL–BMI associations. DESIGN, SETTING AND PARTICIPANTS: Participants were 3898 children in the population-based Longitudinal Study of Australian Children (LSAC) assessed at four biennial waves from ages 4–5 (2004) to 10–11 years (2010). MAIN MEASURES: At every wave, parents completed the Pediatric Quality of Life Inventory, and measured BMI (kgm 2) was converted into BMIz and overweight using international norms. ANALYSES: Linear and logistic regressions. RESULTS: Overweight first became cross-sectionally associated with HRQoL at 6–7 years of age, with linear associations between poorer HRQoL (physical and psychosocial health) and higher BMI developing by 8–9 years and strengthening by 10–11 years. Longitudinal analyses revealed cumulative relationships such that the number of times a child was overweight between the ages 4 and 11 years predicted progressively poorer scores on both physical and psychosocial health at 10–11 years (P-values for trend o0.001). In the weaker reverse associations, children with poor (vs persistently good) physical health at any wave had slightly higher mean BMIz at age 10–11 years, but this difference was small (0.14, 95% confidence interval (CI): 0.04, 0.24) and not cumulative; results for psychosocial health were even weaker, with mixed subscale findings. CONCLUSIONS: Middle childhood appears to be the critical period in which HRQoL–BMI comorbidities emerge and strengthen, first among children with clinically relevant conditions, that is, overweight or poor HRQoL, and then more generally across the whole range of BMI. Poorer HRQoL seemed predominantly a consequence of higher BMI, rather than a cause, suggesting that effective promotion of healthy weight could benefit multiple aspects of children’s well-being.
International Journal of Obesity
Keywords: Health -- Obesity; Children; Health -- Body size, BMI, Body image; Health and wellbeing; Health; Children; Body size, BMI, Body image; Obesity; Health and wellbeing